Association of physical fitness, body composition, cardiometabolic markers and adherence to the Mediterranean diet with bone mineral density in perimenopausal women. The FLAMENCO project. Issue 9 (3rd May 2017) - Aparicio, Virginia A.; Ruiz-Cabello, Pilar; Borges-Cosic, Milkana; Andrade, Ana; Coll-Risco, Irene; Acosta-Manzano, Pedro; Soriano-Maldonado, Alberto
ABSTRACT: This study aimed to analyse the association of different components of physical fitness, body composition, cardiometabolic markers and the Mediterranean diet with bone mineral density (BMD) in perimenopausal women, and to test which of these components are independently associated with BMD. The sample comprised 197 perimenopausal women (52.6 ± 4.5 years). Physical fitness was assessed with the "Senior Fitness Test" battery and the handgrip strength and Bruce tests. Fat and lean mass and BMD were measured using dual-energy X-ray absorptiometry. We analysed the markers of metabolic syndrome, C-reactive protein, and components of the Mediterranean diet. Handgrip muscle strength (β = 0.212, P = 0.005), body weight (β = 0.244, P = 0.001), BMI (β = 0.180, P = 0.011) and lean mass (β = 0.379, P < 0.001) were positively associated with BMD. No associations were observed between cardiometabolic markers or the Mediterranean diet with BMD (all P > 0.05). When all relevant indicators of BMD were simultaneously considered, lean mass was the only 1 showing an independent association with BMD (β = 0.392, P < 0.001), explaining 14% of the BMD variability. In conclusion, muscle strength might be a marker of BMD in perimenopausal women. However, lean mass was the only factor independently associated with BMD. Future research to determine whether increasing lean mass through specific exercise-based interventions contributes to increasing BMD is warranted.